2014
DOI: 10.1016/j.pmn.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Care Seeking for Pain in Young Adults with Sickle Cell Disease

Abstract: In individuals with sickle cell disease (SCD), recognizing the cues to an acute pain episode and responding appropriately are important. The purpose of this mixed-methods pilot study is to identify preliminary factors that influence care seeking for pain in young adults with SCD. Responses were received from 69 young adults with SCD, age 18-35 years. The majority of respondents (88%) wait until the pain intensity is an average of 8.7 (± 1.2) on a scale of 1 to 10 before seeking care. Prominent themes influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 25 publications
5
74
0
Order By: Relevance
“…Pain is a central theme in many of the participant responses and in much of the published research about SCD (Jenerette et al, 2013;Platt et al, 1991;Solomon, 2010). The unpredictability and life-altering nature of how pain is encountered and endured was discussed frequently (Pereira, Brener, Cardoso, & Proietti, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pain is a central theme in many of the participant responses and in much of the published research about SCD (Jenerette et al, 2013;Platt et al, 1991;Solomon, 2010). The unpredictability and life-altering nature of how pain is encountered and endured was discussed frequently (Pereira, Brener, Cardoso, & Proietti, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Presumptions of drug seeking and addiction were pervasive among healthcare providers and palpable to the participants Jenerette et al, 2013). The research team believed that the issue of race was an unspoken theme in the interviews.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Useful self-care methods and ways of coping were enumerated, along with death anxiety and fatalism. More recently, Jenerette, Brewer, and Ataga (2014) performed a qualitative study of 69 young adults with SCD, age 18 to 35, regarding pain management, and found that many avoided the ER due to long waiting periods, being perceived as drug seeking, and ER staff lacking knowledge regarding this illness. Another study focused on the fears of adolescents with SCD and their parents regarding transitioning from pediatric services where they received services all of their lives to adult services (Hauser & Dorn, 1999).…”
mentioning
confidence: 99%